Ready to co-create? Considering pre-creation in care service development for older adults in the rural Swedish north - Jonsson, Frida; Carson, Dean B; Nilsson, Patrik; Jonsson, Alexander; Sahay, Ashlyn; Hurtig, Anna-Karin (Umeå University Library, 2024)
Introduction: While co-creation has emerged as a promising approach to address complex problems in health and care systems, few examples exist where scholars have examined what separate stakeholder groups do to enhance their potential to engage in collaborative processes of joint problem-solving. The current study seeks to bridge this knowledge gap by providing empirical insights into the challenges of one stakeholder enacting ‘pre-creation’ to reform care services for older adults in the rural Swedish north through the Storuman Cares 2050 initiative. Methods: This case study draws upon data collected through extensive notetaking of 23 core group meetings within Storuman Cares 2050. The notes were summarized into a database, which also included reflections on how previous experiences with other projects should inform progress as well as deliberations on engagement with co-creation partners. The data was thematically analyzed with themes developed through an inductive approach. Results: Three themes were developed. The first one, ‘getting our house in order’, makes explicit the values, principles, and approaches that a stakeholder might bring to a co-creation process. The second theme, ‘starting close to home’, describes the value of supporting and stimulating internal engagements through demonstrating a commitment and capacity for change. The third theme, ‘reaching out’, details the importance of, but challenges to, engaging with external stakeholders. Conclusion: This case study bridges an important knowledge gap by detailing how one stakeholder navigated past experiences and the history of relationships with diverse stakeholders while trying to support internal engagements and other local voices when aspiring to co-create. By introducing the concept of ‘pre-creation’ as encompassing the enhancement of an organization’s potential to engage in complex processes of joint problem-solving, the findings provide a stimulus for scholars to further explore what separate stakeholder groups do to enable them to ...